1996
DOI: 10.1002/(sici)1097-0045(199603)28:3<139::aid-pros1>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression of growth factors and their receptors during castration‐induced involution and androgen‐induced regrowth of rat prostates

Abstract: ABSTRACT:To find candidates for the mediator of the growth-promoting action of androgen in rat prostates, the changes in the steady-state levels of mRNAs coding for several growth factors and their receptors were examined by Northern blot analysis during castration-induced involution, and subsequent regrowth induced by androgen in the ventral and dorsolateral lobes. The changes in the growth factor systems and a typical secretory protein in the ventral lobe were similar to, but more prominent than, those in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
6
39
0
1
Order By: Relevance
“…Among the specific target genes that are downregulated by androgen in normal prostate tissue is the EGFR. Regulation of EGFR expression by androgens is shown to be at the transcriptional level, both in normal prostate tissue and prostate cancer (PCa) cell lines (Brass et al, 1995;Ravenna et al, 1995;Nishi et al, 1996;Itoh et al, 1998;Schwartz et al, 1998;Hammarsten et al, 2007;Pignon et al, 2009). This regulation seems to be negatively regulated in normal cells and upregulated in PCa, especially in androgen-independent PCa.…”
Section: Cross-talk Between Androgen Receptors and Egfr Signalling Pamentioning
confidence: 99%
See 2 more Smart Citations
“…Among the specific target genes that are downregulated by androgen in normal prostate tissue is the EGFR. Regulation of EGFR expression by androgens is shown to be at the transcriptional level, both in normal prostate tissue and prostate cancer (PCa) cell lines (Brass et al, 1995;Ravenna et al, 1995;Nishi et al, 1996;Itoh et al, 1998;Schwartz et al, 1998;Hammarsten et al, 2007;Pignon et al, 2009). This regulation seems to be negatively regulated in normal cells and upregulated in PCa, especially in androgen-independent PCa.…”
Section: Cross-talk Between Androgen Receptors and Egfr Signalling Pamentioning
confidence: 99%
“…The EGFR protein binds the epidermal growth factor (EGF) and plays an important role in regulating cellular growth and function (Traish and Wotiz, 1987;St-Arnaud et al, 1988;Nishi et al, 1996;Itoh et al, 1998;Migliaccio et al, 2006;Bonaccorsi et al, 2004Bonaccorsi et al, , 2007Léotoing et al, 2007). Binding EGF to EGFR modulates cellular function by activating EGFR through autophosphorylation, which results in a downstream cascade that leads to increased cellular proliferation (Migliaccio et al, 2006).…”
Section: Cross-talk Between Androgen Receptors and Egfr Signalling Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel changes in the epithelium and prostatic vasculature suggests that the vascular cells may be responding to changes in expression of angiogenic factors secreted by the epithelium. A number of studies have shown that expression of a variety of angiogenic factors, including VEGF, VEGF-B, placental growth factor, and FGF-2 are regulated by androgens in whole prostate or cultured prostate epithelial cells (14)(15)(16)(17)(18)(19)(20)(21). As recent studies have indicated that expression of VEGF is necessary not only for initial vascularization but also for maintenance of some normal adult capillary beds (22), decreased production of VEGF or other angiogenic factors by the prostatic epithelium or stroma may be responsible for the vascular regression observed after castration.…”
Section: Discussionmentioning
confidence: 99%
“…This was the ®rst polypeptide growth factor to be implicated as an andromedin, that is, a factor synthesized in the stromal compartment that indirectly mediates androgen action on prostate epithelial cells to in¯uence their differentiation and function. 26,27,30,31 Studies by Nishi et al 32 have demonstrated that levels of steady state mRNA for FGF-2, KGF and FGFR1 increased 2 ± 4-fold in the dorsolateral rat prostate following castration. Hence subtle changes following castration (ie elaboration of the FGFR1 gene not normally expressed in differentiated epithelium 33 ) may facilitate disease progression to a form that is independent of androgens and stroma.…”
Section: Peptide Growth Factorsmentioning
confidence: 99%